(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Design decisions normally consider the building’s operational phase as the main criterion to reduce energy expenses in a building. In less efficient buildings, reducing the operational energy becomes the most important aspect to address in the design, construction and operational phases, for it represents the highest life cycle energy flow. However, energy-efficient solutions often reduce operational energy demand by increasing the building’s embodied energy and greenhouse gas emissions, which have been overlooked in energy performance analyses. This work aims at investigating the operational energy and the consequent embodied impacts resulting from the retrofit of the window frame of mixed-mode office buildings located in a hot climate, with a focus on reducing the cooling energy demand. The method consists of an experimental study based on a case study, in which the EnergyPlus and the SimaPro software tools are used to evaluate the operational energy and the environmental impacts. Results showed that reducing the WWR and increasing the window opening factor conveyed operational energy savings but in some retrofit scenarios tested, these retrofit measures were counterproductive from the CED and GWP perspective. The main scientific contribution of this work is understanding the importance of the building analysis from a life-cycle approach. The results obtained can assist companies and designers to make their decisions from a broader environmental perspective.